2004
DOI: 10.1073/pnas.0306336101
|View full text |Cite
|
Sign up to set email alerts
|

13- cis -retinoic acid suppresses hippocampal cell division and hippocampal-dependent learning in mice

Abstract: The active component of the acne drug Accutane is 13-cis-retinoic acid (RA), and it is highly teratogenic for the developing central nervous system. Very little is known, however, regarding the effect of this drug on the adult brain. Regions of the brain that may be susceptible to RA are those that continue to generate new neurons. In the adult mouse, neurogenesis is maintained in the hippocampus and subventricular zone. This report demonstrates that a clinical dose (1 mg͞kg͞day) of 13-cis-RA in mice significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
171
4
8

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 197 publications
(190 citation statements)
references
References 54 publications
7
171
4
8
Order By: Relevance
“…However, our present findings indicated that normal hippocampal function requires precise adjustment of retinoid-mediated transcription control, and vitamin A nutritional intake is one factor involved in this regulation. Although retinoid signaling hypoexpression could account for aging-related hippocampal dysfunction (Brouillette and Quirion, 2007), vitamin A or RA in excess during adulthood might have disruptive effects (Crandall et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, our present findings indicated that normal hippocampal function requires precise adjustment of retinoid-mediated transcription control, and vitamin A nutritional intake is one factor involved in this regulation. Although retinoid signaling hypoexpression could account for aging-related hippocampal dysfunction (Brouillette and Quirion, 2007), vitamin A or RA in excess during adulthood might have disruptive effects (Crandall et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Functional implication of retinoid signaling in hippocampal plasticity and spatial memory was demonstrated in rodents by knock-out of RAR␤ or RXR␤/␥ receptors (Chiang et al, 1998;Wietrzych et al, 2005), vitamin A deprivation (Misner et al, 2001;Cocco et al, 2002;Etchamendy et al, 2003b), and RA administration (Crandall et al, 2004). Furthermore, dysfunction of retinoid signaling pathway has been hypothesized to be involved in human neurodevelopmental pathologies such as schizophrenia or late-onset Alzheimer's disease (for review, Goodman, 1998Goodman, , 2006Goodman and Pardee, 2003;Palha and Goodman, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Estudos evidenciaram que tanto a carência quanto o excesso de suprimento de retinóides são prejudiciais na fase embriogênica e adulta, demonstrando a importância de se ter um suprimento adequado de retinol (Bonnet et al, 2008;Crandall et al, 2004;Lammer et al, 1985;Maden et al, 1996). No embrião, o ácido retinóico (RA) é imprescindível na morfogênese, atuando no padrão de desenvolvimento anteroposterior, dorsoventral e na formação do tubo neural (Maden et al, 1996).…”
Section: Retinóidesunclassified
“…Neste sentido, um estudo envolvendo administração crônica do 13-cis-RA em camundongos verificou uma redução na taxa de proliferação e neurogênese no hipocampo de camundongos (Crandall et al, 2004). O hipocampo é uma das poucas áreas encefálicas onde ainda ocorre proliferação de neurônios no cérebro maduro (Eriksson et al, 1998).…”
Section: Retinóidesunclassified
See 1 more Smart Citation